Tear Film, Lacrimal Drainage System, and Eyelid Findings in Subjects With Anophthalmic Socket Discharge - Kashkouli, Mohsen Bahmani; Zolfaghari, Roya; Es'haghi, Acieh; Amirsardari, Anahita; Abtahi, Mohammad Bagher; Karimi, Nasser; Alemzadeh, Amirpooya; Aghamirsalim, Mohamadreza (American journal of ophthalmology, 2016)
To compare the results of tear film and lacrimal drainage system tests between anophthalmic socket and normal eye and assess discharge characteristics and frequency of prosthesis removal (questionnaire), eyelid function, and meibomian glad dysfunction (MGD). Prospective masked case control. Subjects (≥6 years and ≥6 months of wearing prosthesis) with unilateral acquired anophthalmic socket discharge were included. Excluded was ocular adnexal abnormality of any reason and incomplete tests. The subjective questionnaire was completed. Blinking rate, lagophthalmos, eyelid laxity, MGD, Schirmer test, tear meniscus height, and dye disappearance test were assessed by a masked examiner. Another masked examiner performed an irrigation test 1 week later and interpreted the scintigraphy images at the end of the study. Included were 50 subjects (mean age: 31.3 years, mean prosthesis wear: 96.1 months). Discharge was frequent or very frequent in 85%, mucoid or mucopurulent in 90%, and moderate to severe in 86% of the subjects. MGD in 58%, lagophthalmos in 80%, and eyelid laxity in 46% were observed. Anophthalmic socket sides showed a significantly lower tear production and higher tear drainage obstruction. Subjects with frequent prosthesis removal had a significantly (P = .02) greater lagophthalmos and blinking rate (P = .04). The blinking rate was also significantly greater in subjects with higher frequency of discharge (P = .04). Tear film impairment (aqueous and lipid) and lacrimal drainage obstruction should be considered in subjects with anophthalmic socket discharge. A significantly higher blinking rate and lagophthalmos were found in subjects with higher frequency of prosthesis removal.